FAKTOR-FAKTOR YANG MEMPENGARUHI OPINI AUDIT GOING CONCERN (Studi Empiris pada Perusahaan Industri dasar dan kimia di BEI Tahun 2015-2020) - Brilian Ayu Kartikasari; Dul Muid (Diponegoro Journal of Accounting, 2022)
This study aims to determine the factors that can affect going concern audit opinion, with the variables tested are financial condition, leverage, profitability, last year's audit opinion and going concern audit opinion. The object of research used is companies in the basic and chemical industry sectors listed on the Indonesia Stock Exchange from 2015-2020. population of this research there are 78 companies and samples that meet the criteria there are 35 companies while only 200 observations were made Going concern audit opinion is measured by a dummy variable for 1 to receive a going concern audit opinion and 0 for the opposite. Hypothesis testing used logistic regression testing and spss 24 applications. The result of this research is that financial condition, leverage,  have no effect on going concern audit opinion. while profitability and last year's audit opinion had a significant influence on the going concern opinion.